1994
DOI: 10.1177/001872679404700806
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Organizational Commitment and Perceived Management Style: A Comparison of Public and Private Sector Employees

Abstract: Organizational commitment and perceived management styles were examined using survey responses from 1418 employees from both public (N = 474) and private (N = 944) sector organizations, operating in Australia. Comparisons between the two groups of employees revealed higher commitment among private sector employees. These differences were consistent with differences in perceived management styles. In agreement with previous research, factor analysis unveiled that the concept of organizational commitment was mul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
88
1
13

Year Published

1999
1999
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(108 citation statements)
references
References 56 publications
4
88
1
13
Order By: Relevance
“…There are indications that higher levels of alienation among public and private sector employees (Zeffane, 1994), welfare agency workers (Aiken & Hage, 1966) and engineers (Greene, 1978) have been connected to formalization. Furthermore, there is a view point that accepts that formalization reduces stress through decrease of conflict and ambiguity role, providing guidance and clarifying job responsibility (Adler & Borys, 1996).…”
Section: Formalizationmentioning
confidence: 99%
See 1 more Smart Citation
“…There are indications that higher levels of alienation among public and private sector employees (Zeffane, 1994), welfare agency workers (Aiken & Hage, 1966) and engineers (Greene, 1978) have been connected to formalization. Furthermore, there is a view point that accepts that formalization reduces stress through decrease of conflict and ambiguity role, providing guidance and clarifying job responsibility (Adler & Borys, 1996).…”
Section: Formalizationmentioning
confidence: 99%
“…Empirical evidence demonstrates that in an effort of achieving organizational control, centralized decision making is implemented and this action results in employee alienation (Zeffane, 1994). Higher levels of alienation between the public and the private welfare agencies (Aiken & Hage, 1966) and public sector telecommunication workers (Zeffane, 1993) are connected with centralization.…”
Section: Centralizationmentioning
confidence: 99%
“…For instance, if salespeople are concerned about losing their jobs, there is very little chance that they will be willing to exert considerable effort in their job. To this end, aspects of management styles (e.g., degree of management emphasis on flexibility and adaptation perceived by employees) that have been found to have a significant consequences for employee commitment (Zeffane, 1994) may be used to enhance affective commitment and thus increase the practice of ASB among retail salespeople.…”
Section: Managerial Implicationsmentioning
confidence: 99%
“…In literature, there is inconsistency about the impact of this variable. For example, some scholars reported poor commitment on the part of private sector employees (e.g., Moon, 2000;Zeffane, 1994) while some other scholars reported high commitment for private sector employees (e.g., Balfour & Wechsler, 1990). Still some other studies reported no difference (e.g., Steinhaus & Perry, 1996).…”
Section: Discussionmentioning
confidence: 99%